Ergonomical Assessment on Hand Operated Chaff Cutter by Rural Women Workers - Akki, Sathish; Bangi, Nirmala; Batta, Suresh; Basani, Nagaraj; Ch, Balachand (International Journal of Bio-resource and Stress Management, 2021)
A study was conducted to ease the fodder cutting operations a commercially available hand chaff cutter (Sokhiya Agricultural Industries, Jaipur, India) during 2019–20 in the Department of Farm Machinery and Power Engineering at College of Agricultural Engineering, Sangareddy, Telangana, India. The assessment was done using with 3 different age group female workers who regularly feed to the animals to assess its suitability for workers of the southern region of India. The parameters used for the Ergonomical evaluation include machine operation at different forces are heart rate, pulse rate, oxygen consumption rate, and energy expenditure rate. The average heart rate for female subjects of P1, P2 and P3 was recorded before the operation is 79, 76 and 81 beats min-1 and after the operation is 109, 108 and 113 beats min-1 for various fodders. The average pulse rate for female subjects of P1, P2, and P3 was recorded before the operation is 62, 68, and 63 beats min-1 and after the operation is 80, 80, and 82 beats min-1 for various fodders. The average oxygen consumption rate and energy expenditure rate of female subjects of P1, P2 and P3 were found to be 0.61, 0.59 and 0.66 liter min-1, and 12.68, 12.36 and 13.74 KJ min-1 respectively after operation of chaff cutter. The physiological parameters are heart rate, pulse rate, oxygen consumption rate, and energy consumption rate increased more rapidly for all age group female workers after operation of chaff cutter with 3 various fodders.